Study of the X(3872) and Y(4260) in B0→J/ψπ+π-K0 and B-→J/ψπ+π-K- decays - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2006)
We present results of a search for the X(3872) in B0→X(3872)KS0, X(3872)→J/ψπ+π-, improved measurements of B-→X(3872)K-, and a study of the J/ψπ+π- mass region above the X(3872). We use 232×106 BB̄ pairs collected at the Υ(4S) resonance with the BABAR detector at the PEP-II e+e- asymmetric-energy storage rings. The results include the 90% confidence interval 1.34×10-6